2023
DOI: 10.1021/acsami.3c15660
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembling Peptides with Insulin-Like Growth Factor Mimicry

Abhishek Roy,
Joseph B. Dodd-o,
Alicia S. Robang
et al.

Abstract: Growth factor (GF) mimicry involves recapitulating the signaling of larger molecules or cells. Although GF mimicry holds considerable promise in tissue engineering and drug design applications, difficulties in targeting the signaling molecule to the site of delivery and dissociation of mimicking peptides from their target receptors continue to limit its clinical application. To address these challenges, we utilized a self-assembling peptide (SAP) platform to generate synthetic insulin-like growth factor (IGF)s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Moreover, the electrochemically active surface areas (ECSAs) of the prepared electrocatalysts were calculated using double-layered capacitance ( C dl ) measurements, employing diverse scan rates ranging from 0.2 to 0.3 V ( vs. Hg/HgO). 37 The resulting cyclic voltammetry (CV) curves are presented in Fig. S8 †.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the electrochemically active surface areas (ECSAs) of the prepared electrocatalysts were calculated using double-layered capacitance ( C dl ) measurements, employing diverse scan rates ranging from 0.2 to 0.3 V ( vs. Hg/HgO). 37 The resulting cyclic voltammetry (CV) curves are presented in Fig. S8 †.…”
Section: Resultsmentioning
confidence: 99%
“…Table lists all of the peptides studied in this article. We evaluated the differences in the nanofiber structure formed by the following self-assembling peptides conjugated with the bioactive peptide mimics: (1) the vascular endothelial growth factor (VEGF-A) bioactive mimic that provides a scaffold for angiogenesis, (2) the insulin-like growth factor (IGF-1) mimic that has several functions including downstream signaling and proliferation of somatic cells, and (3) SBP3, a mutated ACE2 receptor binding domain fragment, which binds (data not shown) to the spike protein of the SARS-Cov2-RBD-bound ACE2 complex. The efficacy of these systems from in vivo and in vitro studies, as well as the rational design of the bioactive peptide mimics, is reported elsewhere. ,, By applying the one-dimensional (1D) solid-state NMR experiment 1 H– 13 C cross-polarization magic angle spinning (CPMAS), we were able to identify the amino acids involved in the nanofiber structure and evaluate the structural order of the peptide samples. We discovered that all three of the hypothesized structural outcomes are possible.…”
Section: Introductionmentioning
confidence: 99%
“… 12 14 The efficacy of these systems from in vivo and in vitro studies, as well as the rational design of the bioactive peptide mimics, is reported elsewhere. 6 , 11 , 15 By applying the one-dimensional (1D) solid-state NMR experiment 1 H– 13 C cross-polarization magic angle spinning (CPMAS), we were able to identify the amino acids involved in the nanofiber structure and evaluate the structural order of the peptide samples. We discovered that all three of the hypothesized structural outcomes are possible.…”
Section: Introductionmentioning
confidence: 99%